Cervico-ocular function in patients with spasmodic torticollis. Issue 1 (January 1991) - Stell, R; Gresty, M; Metcalfe, T; Bronstein, A M
Abstract : The cervico-ocular (COR) and active and passive vestibulo-ocular reflexes (VOR) were measured in seven patients with spasmodic torticollis (ST) and six normal controls. The COR was found to be weak or absent in both groups. The VOR gain was similar in the two groups but five patients had a significant asymmetry of the response. There was no evidence of abnormal cervico-vestibular interaction during active head rotation. The study suggests that the VOR asymmetry frequently found in ST cannot be explained on the basis of an abnormal cervical input.